2020
DOI: 10.3390/v12070734
|View full text |Cite
|
Sign up to set email alerts
|

Hsv-1 Endocytic Entry into a Human Oligodendrocytic Cell Line Is Mediated by Clathrin and Dynamin but Not Caveolin

Abstract: Endocytosis is a pathway used by viruses to enter cells that can be classified based on the proteins involved, such as dynamin, clathrin or caveolin. Although the entry of herpes simplex type 1 (HSV-1) by endocytosis has been documented in different cell types, its dependence on clathrin has not been described whereas its dependence on dynamin has been shown according to the cell line used. The present work shows how clathrin-mediated endocytosis (CME) is one way that HSV-1 infects the human oligodendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 80 publications
(87 reference statements)
1
11
0
1
Order By: Relevance
“…However, the role of clathrin in entry into C10 or CHO-HVEM cells had not been assessed prior to this study. Moreover, recent work has suggested that HSV-1 entry into a human oligodendrocytic cell line (HOG) depends on clathrin ( 92 ). Therefore, HSV-1 may utilize CME in a cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of clathrin in entry into C10 or CHO-HVEM cells had not been assessed prior to this study. Moreover, recent work has suggested that HSV-1 entry into a human oligodendrocytic cell line (HOG) depends on clathrin ( 92 ). Therefore, HSV-1 may utilize CME in a cell-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding viral infection, there are studies showing a dependence on both clathrin and cholesterol for cell entry, as in the case of varicella-zoster virus (VZV) ( Hambleton et al, 2007 ), type C food-and-mouth- disease virus (FMDV) ( Martín-Acebes et al, 2007 ), Crimea-Congo hemorrhagic fever virus (CCHFV) ( Simon et al, 2009 ), Japanese encephalitis virus (JEV) ( Yang et al, 2013 ) and HIV-1 ( Praena et al, 2020 ). Besides, viruses internalized by clathrin may require cholesterol and/or SM to escape from the endocytic vesicle via fusion.…”
Section: Membrane Rafts In Endocytosismentioning
confidence: 99%
“…This antipsychotic, brand name Thorazine in the United States, has been reported to have broad antiviral activity, including against the RNA viruses Chikungunya (CHIKV), 8 Crimean-Congo hemorrhagic virus (CCHFV), 8 Dengue (DENV), 9 Ebola (EBOV), 8 Hepatitis A (HepA), 10 Hepatitis C (HCV), 8,11 Human Immunodeficiency virus (HIV), 8 Human Parechovirus (HPEV-1), 12 Influenza, 13 Japanese Encephalitis Virus ( JEV), 8 Junin ( JV), 14 Measles, 15 Middle Eastern respiratory syndrome coronavirus (MERS-CoV), 8 Rabies (RABV), 16 SARS-CoV-1, 8 SARS-CoV-2, 5,8 Semliki Forest Virus (SFV), 8,17 Sindbis (SINV), 17 Vesicular Stomatitis (VSV), 8 West Nile Virus (WNV), 8 and Zika 8,18 ; and the DNA viruses Adenovirus, 19 Epstein-Barr (EBV), 20 Herpes Simplex (HSV-1, HSV-2), 21,22 Human Herpes (HHV-8), 23 Human Papilloma (HPV), 24 Human polyomavirus 2 also called John Cunningham ( JCV), 25 and Simian virus (SV40). 26…”
Section: The Most Extensive Information Is Available On Chlorpromazinementioning
confidence: 99%
“…HIV 8 In vitro Entry HPEV 12 In vitro Entry HPV-16 24 In vitro Entry HSV-1 21,22 In vitro Entry(cme)…”
Section: Model Site Of Viral Inhibitionmentioning
confidence: 99%
See 1 more Smart Citation